Asam mefenamat Efek Rekristalisasi Konvensional dan Dengan Bantuan Ultrasonik terhadap Karakteristik Kristal Asam Mefenamat - La Ode Akbar Rasydy; Hilda Damayanti; Adefia Femalda; Ari Yuniarto; Ikhsan Nazar Arrahman; Rifki Saldi A. Wahid (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2025)
Mefenamic acid is classified as a Biopharmaceutical Classification System (BCS) Class II drug. Crystallisation techniques can significantly influence the critical properties of mefenamic acid crystals, an essential consideration in the pharmaceutical industry. This study investigates the effect of recrystallisation on the morphology and particle size of mefenamic acid crystals using ethyl acetate as the solvent.  Recrystallisation was conducted using both conventional and ultrasonic-assisted methods. The yield was calculated, and characterization was performed to determine the crystal properties, shape, and particle size using polarized microscopy, X-ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR). The results showed that conventional recrystallisation yielded 25.078%, while ultrasonic-assisted recrystallisation at 50 W, 60 W, 70 W, and 80 W yielded 43.47%, 47.71%, 51.90%, and 50.20%, respectively. Skewness and kurtosis values for the average crystal length and width indicated a normal distribution. XRD analysis revealed that the diffraction peak intensity of conventionally recrystallised crystals became narrow. In contrast, the diffraction peak intensity of ultrasonically assisted crystals broadened. FTIR results demonstrated that the recrystallisation process did not alter the fundamental chemical structure of mefenamic acid. Recrystallisation methods influence crystal shape and size, with ultrasonic-assisted techniques producing crystals of smaller average size than those obtained through conventional methods.